Preliminary study on geology, mineral potential and characteristics of hot springs from Dallol area, Afar rift, northeastern Ethiopia: implications for natural resource exploration - Solomon Gebresilassie, Haylay Tsegab, Kurkura Kabeto, . (2011)
Dallol area is located in Afar region of northeastern Ethiopia. From west to east, the geology of the area is characterized by: i) Neoproterozoic metavolcanics and metasediments, ii) Quaternary alluvial fan deposits and red beds, iii) a transitional zone of mud and salt mixture, and iv) evaporites, which consist of rock salt (commonly halite and potash) and sulfur/sulfides.